Filtering the Flow, Preserving the Terrace: Islamic Wisdom for Survival and Development in the Age of Globalisation - Hamdan Maghribi; Nuuri Syahdiah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines the complex interaction between globalisation and cultural diversity from an Islamic perspective, a significant challenge contemporary Muslims face.Common responses often get caught in an unproductive dichotomy between reactionary rejection and uncritical assimilation,thus requiring a more sophisticated and balanced framework for principled cultural engagement.The research gap addressed by this study lies in the tripartite synthesis that has not been systematically undertaken in the academic literature, which tends to analyse these thinkers separately or in a two-way comparison.Aiming to construct a holistic model of Islamic cultural interaction,this study employs a comparative-analytical methodology on the corpus of works of three prominent Islamic thinkers from different eras: al-Ghazālī (classical),Ibn Taimiyyah (medieval),and Seyyed Hossein Nasr (contemporary),focusing on their methodological principles to avoid anachronism.The main finding of this research is a complementary and coherent three-layered model.The first layer,taken from al-Ghazālī,presents a pragmatic epistemological filter for assessing foreign knowledge and culture based on the principle of maṣlaḥah (public interest) and its compatibility with maqāṣīd syarī‘ah.The second layer,built on the thought of Ibn Taimiyyah, functions as a theological bulwark protecting core identity through the concepts of tasyabbuh (prohibited imitation) and bid‘ah (religious innovation),which preserve the integrity of creed and ritual.Inspired by Seyyed Hossein Nasr,the third and most fundamental layer offers a profound metaphysical critique,diagnosing globalisation as a universal manifestation of desacralised Modernity,and calling for restoring “Tradition” as an authentic cultural foundation.This synthesis model has proven more resilient and sophisticated than the common binary approach.The implications of this research are significant both theoretically and practically.It offers a principled,critical,and balanced framework for Muslims to engage with the global world.This model provides an intellectual toolkit that can be applied to assess complex contemporary issues such as global Islamic finance,gender discourse,and the digital media economy,thereby encouraging confident and constructive engagement while maintaining religious integrity and contributing to international discourse.